Patient perceptions of tuberculosis transmission: A qualitative study within a tuberculosis cluster - Dyah Wulan Sumekar Rengganis Wardani; Endro Prasetyo Wahono; Bayu Anggileo Pramesona (Universitas Aisyah Pringsewu, 2022)
Significant tuberculosis (TB) spatial-temporal cluster provides where the vulnerable person lives and indicates the possibility of local transmission. Some previous studies showed that there was TB spatial-temporal cluster in some areas, but only few have studied the patient perception of the transmission. The aims of this research are to study the experience and interpretation of the transmission mechanism of smear-positive TB patients in spatial-temporal clusters in Bandar Lampung and identify the possibility of local transmission. A phenomenology qualitative study was performed to identify the experience and interpretation Numbers of samples were 15 patients. Information collected in this research includes TB transmission sources, contact duration and transmission mechanism; which were obtained through in-depth interviews using questionnaires. Data was analyzed using a qualitative approach. Results showed that informants’ perception of TB transmission sources was not from other informants in the clusters, but from in-house contacts, neighbors, and work colleagues. The duration of first contact until informants were diagnosed as TB patients were from three months to some years. The transmission mechanism consisted of speaking directly, treating patients with TB, drinking with the same glass and smoking on the same cigarette. Therefore, TB control programs should consider local transmission and its mechanism for a better TB intervention. Abstrak: Cluster spasial – temporal tuberkulosis (TB) yang signifikan menyediakan informasi dimana orang yang rentan berada dan menunjukkan kemungkinan penularan lokal. Beberapa penelitian sebelumnya menunjukkan adanya TB spasial – temporal cluster di beberapa daerah, tetapi hanya sedikit yang mempelajari persepsi pasien terhadap penularan. Penelitian ini bertujuan untuk mempelajari pengalaman dan interpretasi tentang mekanisme penularan pasien TB BTA positif di cluster spasial – temporal TB di Bandar Lampung dan mengidentifikasi kemungkinan penularan lokal. Penelitian kualitatif fenomenologi dilakukan untuk mengidentifikasi pengalaman dan interpretasi tersebut dengan jumlah sampel 15 pasien. Informasi yang dikumpulkan meliputi sumber penularan TB, lama kontak dan mekanisme penularan; yang diperoleh melalui wawancara mendalam dengan menggunakan kuesioner. Analisis data menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa persepsi informan tentang sumber penularan TB bukan dari informan lain di cluster, melainkan dari kontak rumah, tetangga, dan rekan kerja. Lama kontak pertama sampai informan terdiagnosis sebagai pasien TB berkisar antara tiga bulan hingga beberapa tahun. Mekanisme penularannya berupa berbicara langsung, mengobati penderita TBC, minum dengan gelas yang sama dan merokok dengan rokok yang sama. Oleh karena itu, program pengendalian TB harus mempertimbangkan penularan lokal dan mekanismenya untuk intervensi TB yang lebih baik.